2014
DOI: 10.7224/1537-2073.2012-046
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Health-Related Quality of Life Among Older People with Multiple Sclerosis

Abstract: Background: This study was conducted to determine which factors (clinical and demographic) are associated with mental and physical health-related quality of life (HRQOL) among people with multiple sclerosis (MS) aged 60 years and older. Methods: Data were collected at four MS centers on Long Island, New York, from a total of 211 patients. Three surveys were administered that collected demographic information and included validated questionnaires measuring quality of life (QOL), cognition, depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 56 publications
(74 reference statements)
4
12
0
5
Order By: Relevance
“…Moreover, the results of the present study indicated no relationship between the mean score of Quality of Life and other variables, except for marital status; as the married elderlies reported higher Quality of Life than others (P=0.009) which is consistent with the results of some studies (Jadidi et al 2011;Hajian-Tilaki, Heidari & Hajian-Tilaki 2017;Shi et al 2017;Wang et al 2017b;Zhou & Hearst 2016). However the results were inconsistent with some other studies (Buhse, Banker & Clement 2014). In addition, some studies indicate that elderly people with higher educational level have better health status (Chen, Feng & Li 2014;Dai et al 2016;Tkatch et al 2016).…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, the results of the present study indicated no relationship between the mean score of Quality of Life and other variables, except for marital status; as the married elderlies reported higher Quality of Life than others (P=0.009) which is consistent with the results of some studies (Jadidi et al 2011;Hajian-Tilaki, Heidari & Hajian-Tilaki 2017;Shi et al 2017;Wang et al 2017b;Zhou & Hearst 2016). However the results were inconsistent with some other studies (Buhse, Banker & Clement 2014). In addition, some studies indicate that elderly people with higher educational level have better health status (Chen, Feng & Li 2014;Dai et al 2016;Tkatch et al 2016).…”
Section: Discussionsupporting
confidence: 68%
“…6,7 Previous research has found patient physical disability to be associated with mental health challenges as well as reduced physical QOL. 46,47 Interestingly, the present patient sample exhibited a relatively low level of neurologic disability, as measured by the EDSS, and most patients were within 5 years of symptom onset, demonstrating that QOL is significantly affected in the early stages of the disease. In addition, EDSS scores were significantly correlated with FSS scores but not with PSQI scores.…”
Section: Discussionmentioning
confidence: 63%
“…Education and disease duration were not associated with QOL, similar to the results of previous studies. 31,48 In contrast, Buhse et al 47 showed that less education (high school or less, compared with at least some college) was negatively associated with mental HRQOL. Some limitations of this study should be mentioned.…”
Section: Discussionmentioning
confidence: 94%
“…Diseases (degenerative) of the osteoarticular system, the accompanying pain as well as gradual muscle weakness progress with age and cause the majority of older people to have limited or no ability to perform basic activities of daily living (ADL). This in turn, causes growing frustration and discomfort, resulting in symptoms of depression [8][9][10][11][12][13]. In a study of 1634 elderly people with symptoms of depression, Brazilian authors found diffi culty performing ADLs in both genders.…”
Section: Discussionmentioning
confidence: 99%
“…Cho ro by (zwy rod nie nio we) ukła du kost no -sta wo we go, to wa rzy szą cy im ból oraz stopnio we osła bie nie si ły mię śnio wej po stę pu ją wraz z wie kiem i pro wa dzą u więk szo ści lu dzi star szych do ogra ni cze nia lub nie mo żno ści wy ko na nia pod stawo wych czyn no ści co dzien ne go ży cia. To z ko lei powo du je na ra sta ją cą fru stra cję i po gor sze nie sa mo poczu cia, a w efek cie wy stą pie nie ob ja wów de pre sji [8][9][10][11][12][13]. Au to rzy bra zy lij scy prze pro wa dzi li ba da nia w gru pie 1634 star szych osób z ob ja wa mi de pre sji i stwier dzi li, że za rów no u mę żczyzn, jak i u ko biet wy stę pu ją trud no ści w wy ko ny wa niu czyn no ści ży cia co dzien ne go (ADL).…”
Section: Dys Ku Sjaunclassified